Stability of Structures : Principles and Applications - Yoo, Chai H. and Lee, Sung C.; Lee, Sung Chil (Amsterdam ; Elsevier, 2011)
"The current trend of building more streamlined structures has made stability analysis a subject of extreme importance. It is mostly a safety issue because Stability loss could result in an unimaginable catastrophe. Written by two authors with a combined 80 years of professional and academic experience, the objective of Stability of Structures: Principles and Applications is to provide engineers and architects with a firm grasp of the fundamentals and principles that are essential to performing effective stability analysts"--
Machine generated contents note: Preface XI 1. Buckling of Columns 2. Special Topics in Elastic Stability of Columns 3. Beam-Columns 4. Continuous Beams and Rigid Frames 5. Torsion in Structures 6. Torsional and Flexural-Torsional Buckling 7. Lateral-Torsional Buckling 8. Buckling of Plate Elements 9. Buckling of Thin Cylindrical Shell Elements 10. Buckling of General Shell Elements Index .
Keywords: Structural stability; Safety factor in engineering